The Concept of Consciousness in Sri Aurobindo’s Aesthetics - Tamošaitytė, Daiva (Acta Orientalia Vilnensia, 2001)
This article discusses the aesthetic conception of Sri Aurobindo, and concentrates on his concept of consciousness. Considering art as manifestation of one of the highest levels of Divine consciousness, Supermind, Sri Aurobindo formulates the concept of the future poetry and art, which is based on the harmonization of all the levels of human being. His critical insight into cultural heritage of East and West leads him to the possibility to proclaim art as a transcendental action, which can transform the Being itself by the force of Supermind. The aim of the present article is to define the main features of the novelty of Sri Aurobindo’s aesthetic concept and to discuss its essential categories and significance in the light of consciousness. In the article hermeneutic and historical methods have been used.